an investigation into linguistic features of material processes in “perfect spy” by larry berman versus its vietnamese translational version by đỗ hùng - Đặng,Thị Cẩm Ngọc (2015)
The system of transitivity belongs to one mode of the ideational metafunction, that is, the experiential one which is a source for construing our experience in terms of configuration of a process, participants and circumstances. Out of three main process types in transitivity system, Material process takes up an ample room in written form. Consequently, the aim of the study is to focus on the similarities and differences in the Material process in ―Perfect Spy‖ by Larry Berman versus its Vietnamese translational equivalent ―Điệp Viên Hoàn Hảo‖ by Đỗ Hùng in order that the problems related to realizing, usage and applying the material process will be drawn from this study. After reading the English work an its Vietnamese version, I pick out 1684 samples related to the material process from the English work ―Perfect Spy‖ and its Vietnamese version ―Điệp Viên Hoàn Hảo‖. Both qualitative and quantitative information taken from the samples which is extracted from the work ―Perfect Spy‖ by Larry Berman and in its Vietnamese version is the basic for drawing the implications for teaching and learning material process as well as their application for translation and interpretation. In addition, it simultaneously, encourages those who are interested in English grammar from English grammar from Functional approach to do.